The predictive value of the modified early warning score for admission to the intensive care unit in patients with a hematologic malignancy – A multicenter observational study - van Mourik, Niels; Oomen, Jesse J.; van Vught, Lonneke A.; Biemond, Bart J.; van den Bergh, Walter M.; Blijlevens, Nicole M.A.; Vlaar, Alexander P.J.; Müller, Marcella C.A. (Intensive & critical care nursing, 2023)
The modified early warning score (MEWS) is used to detect clinical deterioration of hospitalized patients. We aimed to investigate the predictive value of MEWS and derived quick Sequential Organ Failure Assessment (qSOFA) scores for intensive care unit admission in patients with a hematologic malignancy admitted to the ward. Retrospective, observational study in two Dutch university hospitals. Data from adult patients with a hematologic malignancy, admitted to the ward over a 2-year period, were extracted from electronic patient files. Intensive care admission. We included 395 patients with 736 hospital admissions; 2% (n = 15) of admissions resulted in admission to the intensive care unit. A higher MEWS (OR 1.5; 95 %CI 1.3–1.80) and qSOFA (OR 4.4; 95 %CI 2.1–9.3) were associated with admission. Using restricted cubic splines, a rise in the probability of admission for a MEWS ≥ 6 was observed. The AUC of MEWS for predicting admission was 0.830, the AUC of qSOFA was 0.752. MEWS was indicative for intensive care unit admission two days before admission. MEWS was a sensitive predictor of ICU admission in patients with a hematologic malignancy, superior to qSOFA. Future studies should confirm cut-off values and identify potential additional characteristics, to further enhance identification of critically ill hemato-oncology patients. The Modified Early Warning Score (MEWS) can be used as a tool for healthcare providers to monitor clinical deterioration and predict the need for intensive care unit admission in patients with a hematologic malignancy. Yet, consistent application and potential reevaluation of current thresholds is crucial. This will enable bedside nurses to more effectively identify patients needing adjunctive care, facilitating timely interventions and improved outcome.